Assessment of stunned and viable myocardium using manganese-enhanced MRI. Issue 1 (7th June 2021) - Spath, Nick B; Singh, Trisha; Papanastasiou, Giorgos; Baker, Andrew; Janiczek, Rob J; McCann, Gerry P; Dweck, Marc R; Kershaw, Lucy; Newby, David E; Semple, Scott
Abstract : Objective: In a proof-of-concept study, to quantify myocardial viability in patients with acute myocardial infarction using manganese-enhanced MRI (MEMRI), a measure of intracellular calcium handling. Methods: Healthy volunteers (n=20) and patients with ST-elevation myocardial infarction (n=20) underwent late gadolinium enhancement (LGE) using gadobutrol and MEMRI using manganese dipyridoxyl diphosphate. Patients were scanned ≤7 days after reperfusion and rescanned after 3 months. Differential manganese uptake was described using a two-compartment model. Results: After manganese administration, healthy control and remote non-infarcted myocardium showed a sustained 25% reduction in T1 values (mean reductions, 288±34 and 281±12 ms). Infarcted myocardium demonstrated less T1 shortening than healthy control or remote myocardium (1157±74 vs 859±36 and 835±28 ms; both p<0.0001) with intermediate T1 values (1007±31 ms) in peri-infarct regions. Compared with LGE, MEMRI was more sensitive in detecting dysfunctional myocardium (dysfunctional fraction 40.5±11.9 vs 34.9%±13.9%; p=0.02) and tracked more closely with abnormal wall motion (r 2 =0.72 vs 0.55; p<0.0001). Kinetic modelling showed reduced myocardial manganese influx between remote, peri-infarct and infarct regions, enabling absolute discrimination of infarcted myocardium. After 3 months, manganese uptake increased in peri-infarct regions (16.5±3.5 vs 22.8±3.5 mL/100 g/min, p<0.0001), but not the remote (23.3±2.8 vs 23.0±3.2 mL/100 g/min, p=0.8) or infarcted (11.5±3.7 vs 14.0±1.2 mL/100 g/min, p>0.1) myocardium. Conclusions: Through visualisation of intracellular calcium handling, MEMRI accurately differentiates infarcted, stunned and viable myocardium, and correlates with myocardial dysfunction better than LGE. MEMRI holds major promise in directly assessing myocardial viability, function and calcium handling across a range of cardiac diseases. Trial registration numbers: NCT03607669 ; EudraCT number 2016-003782-25.